Quality Management in Software Development - M. D. Birulia (Advanced Engineering Research, 2024)
Introduction. The scientific literature examines various approaches to quality management in information technology (IT). The issues of identifying and correcting defects are worked out, and the possibilities for minimizing them are shown. There are materials on quality management in complex engineering processes. At the same time, there is no detailed description of quality management at each stage of the IT product life cycle, including testing. It should be noted that the coordination of software releases is closely related to quality management, but this process is rarely or fragmentarily considered in the literature. Additionally, the interprocess communication is not taken into account; therefore, there is no comprehensive understanding of quality management in the creation, testing and refinement of software. This study is designed to fill these gaps. The research is aimed at presenting a comprehensive approach that links the theory, practice and methods of software quality management.Materials and Methods. Theoretical and applied literature on the subject were studied, analyzed, and reviewed. The author's professional background in managing the quality of IT products was used. The practices of global suppliers of digital goods and services were taken into account. The author has used these materials and methods to study in detail the issues of software testing and code deployment.Results. A comprehensive model of quality management in software development is elaborated, described and presented in the form of a diagram. Its interconnections with the project management model and the product life cycle, namely: analysis, design, development, testing, deployment, and support, are identified. Principles of quality management at each of these stages are specified. The processes and checks during code deployment are systematized and presented in the form of a diagram. Their features are shown in three environments: during development, testing, and production.Discussion and Conclusion. The algorithm allows quality experts to build the sequence of actions to eliminate detected defects in the future, understand the situation when it is possible (or impossible) to deploy code, and determine the moment when the software should be transferred to the user. In addition, the proposed scheme can be the basis for automating code deployment. The solution will reduce development time. As a result, the product will enter the market faster, which will speed up the payback of costs. The implementation of the model created within the framework of this scientific work into the production practice of IT companies presupposes strategic changes. Their implementation requires significant time and other resources; therefore, the overall transformation process should be divided into parts. The proposed approach is adaptable to the needs of various organizations and products. You can work with individual components to create an optimal plan for achieving quality management goals.